The Iraqi Poem in the Age of Multimedia: An Artistic Study (A Case Study of Mushtaq Abbas Ma’an’s La Mutanahiyyat al-Jidar al-Nari)" - Rana Razaq Shlaka, Researcher; Amin Nazari Terizi, Assistant Professor. (lark, 2026)
In recent years, the Iraqi literary scene has witnessed remarkable transformations in poetry as a result of modern technological developments. The poem, once confined to orality and later shifted to writing, has now taken on a renewed digital form through multimedia platforms. This transformation has enabled poets to produce digital poems that transcend the boundaries of the classical written text. Several key factors contribute to understanding these transformations in Iraqi poetry within the multimedia age, most notably cultural and social influences—both global and local—as well as innovations in form. This study aims to shed light on La Mutanahiyyat al-Jidar al-Nari by Mushtaq Abbas Ma’an, a pioneer of digital poetry in the Arab world. In this work, the poem shifts from orality to digitality, relying on hypermedia and incorporating audio-visual elements into the poetic text while breaking away from all traditional poetic conventions.
Keywords: : Iraqi digital poetry, La Mutanahiyyat al-Jidar al-Nari, Mushtaq Abbas Ma’an